Pengaruh Surfaktan Polysorbate dan Lesitin Pada Pelumas Minyak Goreng Terhadap Temperatur Mesin dan Daya - Muhammad Rifqi Aditya Irawan; Haris Puspito Buwono (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The development of the automotive world to date has grown rapidly, especially two-wheeled vehicles. Large temperature changes in lubricating oil viscosity, even if the value is too low, will reduce the lubrication of engine parts, increase friction between metals, and cause engine parts to heat up quickly. Efforts to control and overcome excessive engine heat can replace mineral-based lubricating oils with environmentally friendly and biodegradable lubricating oils. The purpose of this study is to determine the effect of using a mixture of cooking oil and surfactants C64H124O26 and C42H80NO8P as engine lubricants on the power and temperature produced by motorized vehicles. The independent variables of this research are RPM variation and mixture of pure cooking oil with lecithin and polysorbate surfactant (2.5%, 5%, 7.5%). The dependent variables are engine temperature and power. The control variables of this research are testing at room temperature, 4 stroke 125CC matic vehicle, and Raw Material using Palm cooking oil. The test method uses an infrared thermo gun for temperature and Dyno test for the highest power test on the type of Cooking Oil + Polyosrbate 7.5% with an average overall power of 5.872, then for the lowest temperature on the type of Cooking Oil + Polysorbate 2.5% with an average value of 86.2ºC.